Ibnu Sina: A Reconciliation Between Religion, Philosophy, Divinity, Soul, and Islamic Education - Ronaldi, Ronaldi; AM, Rusyadi; Saputra, Riki (Al-Mudarris, 2025)
This research aims to discuss Ibn Sina's thought in harmonizing religion, philosophy, divinity, soul, and Islamic education. As a leading Muslim philosopher, Ibn Sina successfully integrated rationalism and spirituality, especially in the concept of divinity that he designed through the theory of emanation. He also developed a theory of the soul rooted in Aristotelian-Neoplatonic thought, in which the human soul is seen as having different levels in achieving perfection. In the Islamic education system, Ibn Sina emphasized the importance of students' intellectual and moral development and the role of teachers in guiding them towards the perfection of the soul. According to him, education is not only limited to the transfer of knowledge, but also a process of character building and the refinement of human potential. This research uses a literature research method with a qualitative-descriptive approach, namely by reviewing various relevant literature to understand more deeply the thoughts of Ibn Sina. The results showed that the concepts developed by Ibn Sina are still relevant in the world of education and contemporary Islamic philosophy. His thinking provides a balanced perspective between intellect and spirituality, which can be the basis for the development of a more comprehensive and holistic Islamic education.